Needs of fashion and tourism companies from Medellín concerning the hiring of bilingual and multilingual personnel that support their internationalization processes (2023)
It is essential to take into account that to successfully achieve internationalization, companies have to face and overcome some barriers, one of those is the language barrier; for that reason, they hire professionals that have command of foreign languages to help the companies to establish themselves in international territories. The companies from Medellín are not external to the multiple benefits that internationalization can bring to them and to the city’s development since the city has been gradually working on the consolidation of its international relations as a local development engine, leaving behind the economic standard based on the industry in order to enter into the commercial services (Cortés, 2015). Due to that, some universities created language programs with the objective to train professionals that have proficiency in different languages, for example the ECCI University created the Modern Languages program as a response to the needs for internationalization that the companies in the city have. This research aims to identify the needs of fashion and tourism companies in Medellín regarding the hiring of bilingual and multilingual personnel that supports their internationalization processes. Through semi-structured interviews and data collection from 10 fashion and 10 tourism companies, the study delves into the needs of these two clusters, seeking to understand the role that a modern languages professional could play in the internationalization process in fashion and tourism companies, in order to know if the study plan offered by the ECCI University for the Modern Languages program really meets the companies’ needs for internationalization.